PENGARUH PH TERHADAP KUALITAS PRODUK ETANOL DARI MOLASSES MELALUI PROSES FERMENTASI - Sinar Perbawani Abrina Anggraini; Susy Yuniningsih; Mauritsius Melkysedes Sota (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
The energy crisis of fuel is a problem faced by almost every state, predicted fuel reserves only enough oil to meet the world's needs for the next 30 years. Bioethanol is a non-fossil fuel considerable potential and can be used as an alternative fuel. This study aims to determine the effect of pH on ethanol yield and to determine the optimal pH by using a fermentation process raw material molasses. The research variables consisted of fixed and changing research, the materials used are, molasses (molasses), yeast Saccharomyces cerevisiae, NPK, urea, and water, and the tools used, the fermentor, pH meters, and pycnometer. The conclusion of this study, the pH affects the quality of ethanol and the highest levels of ethanol produced at pH 4.5, where the concentration of glucose and yeast performance Sacharomyces cereviseae very optimum at pH 4.5 to produce the ethanol content amounted to 5.6%.